The Role of Spiritual Well-Being and Materialism in Determining Consumers’ Ethical Beliefs: An Empirical Study with Australian Consumers - Chowdhury, Rafi M. M. I.; Fernando, Mario (2013)
A survey was conducted to investigate the relationship of Australian consumers’ lived (experienced) spiritual well-being and materialism with the various dimensions of consumer ethics. Spiritual well-being is composed of four domains—personal, communal, transcendental and environmental well-being. All four domains were examined in relation to the various dimensions of consumers’ ethical beliefs (active/illegal dimension, passive dimension, active/legal dimension, ‘no harm, no foul’ dimension and ‘doing good’/recycling dimension). The results indicated that lived communal well-being was negatively related to perceptions of the active/illegal dimension and the passive dimension and was positively related to perceptions of the ‘no harm, no foul’ dimension and the ‘doing good’/recycling dimension. Lived personal well-being was negatively related to perceptions of the active/illegal dimension and was positively related to perceptions of the ‘no harm, no foul’ dimension and the ‘doing good’/recycling dimension. Lived transcendental well-being was negatively related to perceptions of the passive dimension, the active/legal dimension and the ‘no harm, no foul’ dimension. Lived environmental well-being was negatively related to perceptions of the active/legal dimension and the ‘no harm, no foul’ dimension. The findings also indicated that materialism was positively associated with perceptions of actively benefiting from illegal actions, passively benefiting at the expense of the seller, actively benefiting from questionable but legal actions and benefiting from ‘no harm, no foul’ actions. Public policy implications of the findings and opportunities for future research are discussed.
Keywords: Consumer ethics; Materialism; Spiritual well-being